Nano-mechanical characterization of plasma surface tungstenized layer by depth-sensing nano-indentation measurement - Wu, Hongyan; Li, Yin; Tang, Xiao; Hussain, G.; Zhao, Haofeng; Li, Qingfang; Adedotun, Adetunla (Elsevier, 2015)
Plasma surface tungstenizing was performed on Ti-Al-Nb substrate using the double-glow plasma surface alloying technique. The microstructure and composition of the tungstenized layer were determined by scanning electron microscope, X-ray diffraction and X-ray photoelectron spectroscopy. The mechanical properties of the substrate and the tungstenized layer were characterized by the dynamic micro-hardness and the elastic modulus. The results showed that the tungstenized layer was comprised of three distinct sub-layers namely sediment layer, transition layer and diffusion layer, with a total layer thickness of over 25 mu m. The concentration of the tungsten decreased gradually as the layer depth increased and the continuous change in the tungsten content affects the mechanical properties of the alloyed layer. The dynamic micro-hardness and elastic modulus of the tungstenized layer and substrate were investigated by the depth-sensing nano-indentation measurement under different conditions. According to the findings, the values of dynamic micro-hardness exhibited no significant dependence on the indentation load. However, the elastic modulus of the tungstenized layer tended to decrease as the indentation load was increased. Furthermore, the dynamic micro-hardness and elastic modulus curves of the tungstenized layer revealed a pattern similar to the concentration distribution of the tungsten. Both surface micro-hardness and elastic modulus of plasma alloyed surface gradually decreased with the increase of indentation depth, most probably because of the three different regions in the alloyed layer. As for the mechanical properties, the tungstenized layer exhibited significantly higher dynamic micro-hardness and elastic modulus than the substrate. As the cyclic loading-unloading curves of the substrate and the tungstenized layer showed, the elastic recovery and uniform plastic deformation decrease and the fatigue damage of the tungstenized layer is lower than that of the substrate. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Surface alloying; The tungstenized layer; Surface mechanical properties; Dynamic micro-hardness; Elastic modulus